Haunted by detail. - Balkema, Annette W.; Bernardelli, Francesco; Boomgaard, Jeroen; Braidotti, Rosi; Dietrich, Nikola; Eldahab, Mai Abu; Molnar, Edit; Petresin, Natasa; Senova, Basak (Amsterdam : De Appel Foundation Amsterdam, 2002)
Beltrán, Erick ; Benczúr, Emese ; Claerbout, David ; Holmqvist, Karl ; Kessler, Leopold ; Koo Jeong-a ; Neuenschwander, Rivane ; Sala, Anri ; Scanner ; Snyder, Sean ; Vaglieri, Marco ; Visser, Barbara ; Zaatari, Akram ; Zaki, Tarek
Haunted by detail, De Appel Foundation, Amsterdam, Curatorial Training Programme 2002, 16 November 2002 - 5 January 2003
Engels
boek